God is Beautiful : The Aesthetic Experience of the Quran - Navid Kermani; Translated by Tony Crawford (Malden Polity Press, 2015)
The melodious recitation of the Quran is a fundamental aesthetic experience for Muslims, and the start of a compelling journey of ideas. In this important new book, the prominent German writer and Islamic scholar Navid Kermani considers the manner in which the Quran has been perceived, apprehended and experienced by its recipients from the time of the Prophet to the present day. Drawing on a wide range of Muslim sources, from historians, theologians and philosophers to mystics and literary scholars, Kermani provides a close reading of the nature of this powerful text. He proceeds to analyze ancient and modern testimonies about the impact of Quranic language from a variety of angles. Although people have always reflected on the reception of texts, images and sounds that they find beautiful or moving, Kermani explains that Islam provides a particularly striking example of the close correlation, grounded in a common origin, between art and religion, revelation and poetry, and religious and aesthetic experience. This major new book will enhance the dialogue between Islam and the West and will appeal to students and scholars of Islam and comparative religion, as well as to a wider readership interested in Islam and the Quran.
Include Notes, Glossary, References and Index
Keywords: Aesthetics in the Quran